Association between accompanying duration and anxiety/depression among family caregivers: a prospective cohort study in China during the COVID-19 pandemic - Jiang, Yanhong; Hong, Weiwen; Huang, Lili; Ying, Hongan (Frontiers in Psychiatry, 2024)
IntroductionWhile some studies have explored family caregivers’ anxiety and depression, limited research has been conducted on family caregivers’ anxiety and depression caused by the duration of companionship, resulting in an unclear relationship between the length of accompaniment and the psychological well-being of family caregivers.MethodsThis cohort study was conducted from April 1, 2022, to June 30, 2022 in general surgery. We employed bar graphs and line graphs to illustrate the relationship between accompanying days and anxiety and depression. Additionally, mixed-effects linear regression models were utilized to examine the correlation between accompanying days and the likelihood of anxiety and depression.ResultsThe study had 207 family caregivers, with 23.5% experiencing anxiety and 13.1% experiencing depression. Anxiety and depression scores peaked on day 9, and the incidence rate was the highest for the third group (≥10 days). Family caregivers in the first group (≤4 days) of companionship had significantly higher anxiety (β=0.27, 95% CI 0.16-0.39, p<0.001 in all three models). Those in the second group (5-9 days) and the third group (≥10 days) showed no significant correlation with anxiety scores, except for a negative correlation in Model III (β=-0.15, 95% CI -0.29 to -0.01) for companionship in the third group (≥10 days). Family caregivers in the first group (≤4 days) of companionship had significantly higher depression scores (β=0.19, 95% CI 0.10-0.29, p<0.001 in all three models). Those in the second group (5-9 days) had no significant relationship with depression, while those in the third group (≥10 days) exhibited a small negative correlation in Model II and III (β= -0.02, 95% CI -0.08-0.04). The sensitivity analysis confirms the mixed-effects linear regression findings.ConclusionThere was a positive correlation between the duration of family companionship and anxiety and depression in the early days.